Impact of Reactogenicity After Two Doses of Recombinant Zoster Vaccine Upon Physical Functioning and Quality of Life: An Open Phase III Trial in Older Adults. (12th June 2020) - Schmader, Kenneth E; Levin, Myron J; Chen, Michael; Matthews, Sean; Riley, Megan E; Woo, Wayne; Hervé, Caroline; Grupping, Katrijn; Schuind, Anne E; Oostvogels, Lidia; Curran, Desmond
Abstract: Background: Herpes zoster may significantly impact quality of life (QoL) in older adults. The recombinant zoster vaccine (RZV) is efficacious in adults aged ≥50 and older and is associated with increased reactogenicity compared to placebo. We report here on the impact of reactogenicity of the second RZV dose on the QoL and physical functioning (PF) of vaccine recipients, and summarize findings following both doses. Method: In this single-arm study, 401 adults aged ≥50 and older were enrolled to receive two RZV doses 2 months apart. Change in mean Short Form Survey-36 (SF-36) PF and EuroQol-5 Dimension (EQ-5D) scores, reactogenicity, safety, productivity loss, and healthcare resource utilization were evaluated. Results: In total, 391 (97.5%) participants received dose 2. Post-dose 2, the most common solicited local symptoms were injection site pain (75.1%), erythema (22.4%), and swelling (13.9%), and the most common systemic symptoms were fatigue (46.3%), headache (37.5%), and myalgia (32.9%). Grade 3 solicited (local and systemic) adverse events were reported by 61 (15.6%) participants and were associated with a transient clinically significant decrease in SF-36 PF score on Days 1–2 post-dose 2 that recovered by Day 3. Overall, no clinically important reduction in mean SF-36 PF scores was observed from baseline to post-dose 2 (mean change −0.4), and no quality-adjusted-life-year loss was recorded. Conclusions: Overall, QoL and PF of RZV vaccinees were not affected by vaccine-related reactogenicity. A transient reduction was observed in the first 2 days after RZV vaccination in individuals with Grade 3 adverse events. No safety concerns were identified.